Uso do MLPA para diagnóstico de pacientes com deficiência intelectual e/ou atraso do desenvolvimento sindrômicos - Anisse Marques Chami (2016)
The prevalence of intellectual disability (ID) in general population is estimated to be between 1% to 3%. It is often associated with global developmental delay (GDD) and others important features as congenital malformations and dysmorphisms. This association characterizes syndromic patients with ID. Genetic causes are heterogeneous and responsible for 17,4% to 47,1% of the syndromic ID and/or GDD etiology. One of the main causes between this group are represented by interstitial and subtelomeric chromosomal deletions and duplications which can be diagnosed with different genomic studies techniques. The G-Banding kariotyping allows a broader approach for these genetic alterations diagnosis. Therefore, it has limitations identifying smaller copy number variations (CNVs) like microdeletions and microduplications. MLPA (Multiplex ligation-dependent probe amplification) is an alternative molecular test used to detect these smaller CNVs. It uses probe sets commercially available from its manufacture, MRC Holland®, for a very large range of DNA regions associated to genetic microdeletion/duplications disorders. The present study analyzed MLPA test´s results from 191 syndromic patients with ID and/or GDD from the Medical Genetic UFMG Clinical Center, between October 2013 and October 2015. All the patients had normal karyotype. The main objective of this research was to improve patient´s diagnosis and analyze how MLPA collaborated with this and with genetic counseling. The detections rate for MLPA positive alterations was 15,9% (29/191). To validate the result, each positive case was retested using another MLPA kit and or tested with other molecular technique, like a-CGH (array comparative genome hybridization). They were also investigated singly through the medical records to evaluate the genotype-phenotype correlation and how the test guided the patient diagnosis and management decision. Among the results findings, some clinical suspicions could be confirmed and they represented some of the most common recognizable genetic syndromes: velocardifacial, Williams, Prader-Willi and Sotos syndromes. Also, some rare microdeletion syndromes were identified and some rare chromosomal complex rearrengment (double deletions) that played an expressive role for the patient phenotype. The MLPA improved the clinical genetic assessment for an important portion of patients, although showed a limitations to delineate clearly some genetics findings to some of the patients.